Intact protein mass spectrometry and top-down proteomics. (April 2013) - Whitelegge, Julian
American Society for Mass Spectrometry Sanibel meeting on top-down mass spectrometry St Pete Beach, FL, USA, 24–27 January 2013 Top-down mass spectrometry involves analysis of intact proteins, typically using electrospray ionization, as multiple charging enhances dissociation and thus identification by comparison of precursor and product ion masses with protein sequence databases. Traditionally a low-throughput, precision technology performed on high-resolution Fourier-transform ion cyclotron resonance mass analyzers, top-down proteomics aims to increase throughput for whole proteome analysis while preserving the inherent value of an intact protein mass measurement. This years' American Society for Mass Spectrometry Sanibel meeting brought together established scientists who have demonstrated the viability of the top-down approach and its applicability to virtually all segments of the proteome, mixing them with researchers from diverse areas and with the common interest of advancing top-down into the high-throughput proteomics mainstream. Advances in instrumentation including the orbitrap analyzer, ionization mechanisms, dissociation strategies and informatics, as well as a wide variety of applications, were discussed in depth, leading to the inescapable conclusion that the future for top-down is bright.